Aberrant DNA methylation patterns in diabetic nephropathy - Maghbooli, Zhila (BioMed Central, 2014)
BACKGROUND: The aim of this study was to evaluate whether global levels of DNA methylation status were associated with albuminuria and progression of diabetic nephropathy in a case-control study of 123 patients with type 2 diabetes- 53 patients with albuminuria and 70 patients without albuminuria. METHODS: The 5-methyl cytosine content was assessed by reverse phase high pressure liquid chromatography (RP-HPLC) of peripheral blood mononuclear cells to determine individual global DNA methylation status in two groups. RESULTS: Global DNA methylation levels were significantly higher in patients with albuminuria compared with those in normal range of albuminuria (p = 0.01). There were significant differences in global levels of DNA methylation in relation to albuminuria (p = 0.028) and an interesting pattern of increasing global levels of DNA methylation in terms of albuminuria severity. In patients with micro- and macro albuminuria, we found no significant correlations between global DNA methylation levels and duration of diabetes (p > 0.05). In both sub groups, there were not significant differences between global DNA methylation levels with good and poor glycaemic control (p > 0.05). In addition, in patients with albuminuria, no differences in DNA methylation levels were observed between patients with and without other risk factors including age, gender, hypertension, dyslipidaemia and obesity. CONCLUSIONS: These data may be helpful in further studies to develop novel biomarkers and new strategies for clinical care of patients at risk of diabetic nephropathy.